Experimental evaluation of data fusion algorithm for residual generation in detecting UAV servo actuator fault - Sahwee Z.; Rahman N.A.; Sahari K.S.M. (Multi-Science Publishing Co. Ltd, 2023)
Algorithms; Data fusion; Hardware; Military vehicles; Redundancy; Software reliability; Unmanned aerial vehicles (UAV); Analytical redundancy; Data fusion algorithm; Experimental evaluation; Fault detection algorithm; Hostile environments; Model reference methods; On-board fault detection; Software and hardwares; Fault detection